A Bone Structural Basis for Fracture Risk in Diabetes - Melton, L. Joseph (The Endocrine Society, 2008)
Context: Elevated areal bone mineral density (aBMD) in type 2 diabetes mellitus is inconsistent with increased fracture risk at some skeletal sites. Objectives: Because aBMD is an imperfect surrogate for bone strength, we assessed bone structure and strength more directly using quantitative computed tomography. Design: Diabetic and nondiabetic subjects were evaluated in a cross-sectional study. Setting: Subjects were recruited from a random sample of the Rochester, MN, population. Participants: Forty-nine subjects (28 women and 21 men) with type 2 diabetes were compared with age- and sex-matched nondiabetic controls. Main Outcome Measurements: We measured bone geometry, strength, and volumetric BMD (vBMD) at the hip, spine, and wrist, along with hip aBMD, using central and peripheral quantitative computed tomography and estimated bone load to bone strength ratios at each site. Results: Adjusted for differences in body mass index between cases and controls (29.8 vs. 27.6), hip aBMD was greater in diabetic subjects, but this was accounted for by greater trabecular vBMD. Cortical vBMD was similar in the two groups, as was bone cross-sectional area and cortical thickness. Bone strength measures were generally better in diabetic subjects, but bone loads were higher from their greater weight. Consequently, load to strength ratios (i.e. factor-of-risk) were similar. Conclusions: Patients with type 2 diabetes enjoy little benefit from elevated aBMD in terms of improved bone load to strength ratios. With no deficit in bone density, the rationale for antiresorptive therapy in diabetic patients is uncertain, but potential adverse effects of diabetes on bone quality need more study.